2011
DOI: 10.1242/dev.067264
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis with coat color genotyping identifies an essential role for Skor2 in sonic hedgehog signaling and cerebellum development

Abstract: SUMMARYCorrect development of the cerebellum requires coordinated sonic hedgehog (Shh) signaling from Purkinje to granule cells. How Shh expression is regulated in Purkinje cells is poorly understood. Using a novel tyrosinase minigene-tagged Sleeping Beauty transposon-mediated mutagenesis, which allows for coat color-based genotyping, we created mice in which the Ski/Sno family transcriptional co-repressor 2 (Skor2) gene is deleted. Loss of Skor2 leads to defective Purkinje cell development, a severe reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 44 publications
1
50
0
Order By: Relevance
“…This hypothesis is supported by a recent paper describing a loss-of-function phenotype for mouse Corl2 in mice (Wang et al, 2011). In addition to gross cerebellar defects, homozygous mouse Corl2 mutant mice lack sonic hedgehog expression in Purkinje cells.…”
Section: Discussion Corl Function In Tgf Signaling and Neural Develomentioning
confidence: 61%
“…This hypothesis is supported by a recent paper describing a loss-of-function phenotype for mouse Corl2 in mice (Wang et al, 2011). In addition to gross cerebellar defects, homozygous mouse Corl2 mutant mice lack sonic hedgehog expression in Purkinje cells.…”
Section: Discussion Corl Function In Tgf Signaling and Neural Develomentioning
confidence: 61%
“…Initially, the involvement of Shh signaling in embryonic development of mammal species was discovered. Deprivation of certain molecules of this pathway was found to cause cerebellum atrophy and limb defects in rats (27)(28)(29)(30). Since neoplasms and embryonic development share similar molecular signaling processes, numerous studies have examined and demonstrated the core role of Shh signaling in maintaining tumor growth and cancer cell survival (12).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, it appears that Shox2 is required to maintain proper Shh expression levels in the developing postnatal cerebellum; whether this occurs via direct or indirect regulation of Shh and whether loss of normal SHH levels or loss of SHOX2 directly is responsible for the premature onset of Bmp4 expression has yet to be determined. Since this phenotypic effect is most prominent in the dorsal vermis, factors other than SHOX2 must contribute to Shh regulation in other regions of the cerebellum, such as RORα, SKOR2 or other spatially restricted Purkinje cell specific genes (Gold et al, 2003;Otero et al, 2014;Wang et al, 2011).…”
Section: Shox2 Is Important For Maintaining Shh Expression Levels In mentioning
confidence: 99%
“…Disruption of the balance between these signals can result in medulloblastoma due to the constant activation of the SHH signal and resulting uncontrolled GCP proliferation (Grimmer and Weiss, 2008;Zhao et al, 2008). Despite the pivotal function of SHH in cerebellar development, the upstream regulators that establish and/or maintain the Shh expression pattern in this brain region are only just starting to be uncovered (Gold et al, 2003;Wang et al, 2011;Xenaki et al, 2011). In addition, while a number of studies have demonstrated that BMP signaling can antagonize SHH-mediated GCP proliferation (Grimmer and Weiss, 2008;Rios et al, 2004), the signals responsible for the correct timing and proper balance of cerebellar GCP proliferation and granule cell differentiation have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%